Charting a Research Agenda for the Advancement of Nursing Organizations' Influence on Health Systems and Policy. Issue 3 (September 2020) - Chiu, Patrick; Duncan, Susan; Whyte, Nora
Nursing organizations across Canada play a significant role in influencing and shaping public policy. 2020, the Year of the Nurse and the Midwife, is an opportune time not only to support nurses in building policy leadership but also to explore opportunities to better understand and strengthen the policy advocacy work of nursing organizations. Given various social, political, and economic forces, the nature of organized nursing across Canada is changing significantly. We draw on recent key national and global events including our systematic inquiry into Canada's 2019 federal election, the Year of the Nurse and Midwife, and the Coronavirus pandemic to examine how Canadian nursing organizations respond in highly complex and evolving contexts. We use our observations to offer a vision and chart a research agenda for the advancement of nursing organizations' influence on health systems and policy. Specifically, we focus on three key areas including examining nursing organizations' policy agendas and spheres of influence; nursing organizations' decision-making around policy advocacy tactics and engagement approaches; and the impact of policy advocacy coalitions and networks on nursing organizations' influence.